Four Levitations over Four Notes on Cypriot Literature - Pavlou, Savvas (Études helléniques / Hellenic Studies, 2007)
The author outlines the positive and negative aspects of the relationship between a Helladic centre and the Cypriot periphery. He argues in favour of polycentrism versus Athenian concentrationism.